2007
DOI: 10.1111/j.1744-7410.2007.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology of a “babysitting” symbiosis in brittle stars: analysis of the interactions between Ophiomastix venosa and Ophiocoma scolopendrina

Abstract: . “Babysitting” symbioses between brittle star species involve juveniles of one species and adults of another. During this phenomenon, reported from many localities in the Indo‐Pacific Ocean, juveniles are attached to the disk or lie in the bursa of the adults. The symbiosis between members of Ophiomastix venosa and their host, Ophiocoma scolopendrina, was investigated on the Great Barrier Reef of Toliara (Madagascar) during a 14‐month period. The population of O. scolopendrina only occurs on rocky spurs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Echinoderm recognition through chemodetection is performed by many ectocommensals, and is one of the main parameters that ensures the transgenerational sustainability of symbiotic associations 6 , 16 , 20 , 23 , 44 , 45 . Two ectocommensal symbioses associated with echinoderms and decapods had previously been investigated in order to identify the nature of the chemical signals allowing host selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinoderm recognition through chemodetection is performed by many ectocommensals, and is one of the main parameters that ensures the transgenerational sustainability of symbiotic associations 6 , 16 , 20 , 23 , 44 , 45 . Two ectocommensal symbioses associated with echinoderms and decapods had previously been investigated in order to identify the nature of the chemical signals allowing host selection.…”
Section: Discussionmentioning
confidence: 99%
“…Chemodetection is a very common process completed by many symbiotic organisms to find their hosts, particularly when the symbiosis is obligatory and concerns a specific host. Evidence of host selections triggered by chemical sensing involving echinoderms as hosts have been shown for polychaetes living on asteroids/holothuroids 17 , 18 , shrimps associated with crinoids 19 , ophiuroids associated with other ophiuroids 20 , fishes 21 , 22 and crabs 23 associated with holothuroids, and bivalves 24 , gastropods 16 , crabs 25 , 26 , shrimps 6 , 27 and fishes associated with echinoids 28 . While chemodetection has been proven to play a major role in host selection, it is only recently that it was demonstrated that the symbiotic Harlequin crab Lissocarcinus orbicularis is attracted by the saponins produced by its holothuroid hosts 23 .…”
Section: Introductionmentioning
confidence: 98%
“…Hal tersebut menjelaskan bahwa terjadi kesamaan kebutuhan antara kedua spesies tersebut pada area makroalga terutama alga coklat. Pada beberapa wilayah bebatuan yang tergenang air, seringkali ditemukan O. annulosa yang berasosiasi dengan O. scolopendrina dalam berbagi habitat dan berbagi makanan (Fourgon et al 2003;Fourgon et al, 2007). Ophiocoma erinaceus dapat ditemukan bersama-sama dengan O. dentata di daerah lamun, karena menurut Minarputri et al, (2012) kedua spesies tersebut memanfaatkan area lamun sebagai feeding ground.…”
Section: Densitasunclassified
“…The presence of a speciesspecific chemical cue used in host recognition is evidence of a specialized adaptation that may reflect a fitness advantage. Echinoderms rely on chemical cues to recognize prey items (Sloan & Campbell 1982) as well as associated hosts (Clavico et al 2006, Fourgon et al 2007). In the Florida Keys, Ophiothrix lineata lives primarily in association with Callyspongia vaginalis, and also lives at low frequency (<1%) in the tube sponges Niphates digitalis (Henkel & Pawlik 2005) and Verongula (Aplysina) lacunosa (Kissling & Taylor 1977).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%